Assessing teamwork performance in obstetrics: A systematic search and review of validated tools. (September 2017) - Fransen, Annemarie F.; de Boer, Liza; Kienhorst, Dieneke; Truijens, Sophie E.; van Runnard Heimel, Pieter J.; Oei, S. Guid
Abstract: Teamwork performance is an essential component for the clinical efficiency of multi-professional teams in obstetric care. As patient safety is related to teamwork performance, it has become an important learning goal in simulation-based education. In order to improve teamwork performance, reliable assessment tools are required. These can be used to provide feedback during training courses, or to compare learning effects between different types of training courses. The aim of the current study is to (1) identify the available assessment tools to evaluate obstetric teamwork performance in a simulated environment, and (2) evaluate their psychometric properties in order to identify the most valuable tool(s) to use. We performed a systematic search in PubMed, MEDLINE, and EMBASE to identify articles describing assessment tools for the evaluation of obstetric teamwork performance in a simulated environment. In order to evaluate the quality of the identified assessment tools the standards and grading rules have been applied as recommended by the Accreditation Council for Graduate Medical Education (ACGME) Committee on Educational Outcomes. The included studies were also assessed according to the Oxford Centre for Evidence Based Medicine (OCEBM) levels of evidence. This search resulted in the inclusion of five articles describing the following six tools: Clinical Teamwork Scale, Human Factors Rating Scale, Global Rating Scale, Assessment of Obstetric Team Performance, Global Assessment of Obstetric Team Performance, and the Teamwork Measurement Tool. Based on the ACGME guidelines we assigned a Class 3, level C of evidence, to all tools. Regarding the OCEBM levels of evidence, a level 3b was assigned to two studies and a level 4 to four studies. The Clinical Teamwork Scale demonstrated the most comprehensive validation, and the Teamwork Measurement Tool demonstrated promising results, however it is recommended to further investigate its reliability.